Value Relevance of Environmental, Social and Governance (ESG): Does Profits and Purpose Overlap? - Sund, Lars (2020)
The primary objective of this study is to account for the transformative movements impacting corporate sustainability in the 21st century, as well as empirically examine the historical value relevance of adherence to strong corporate sustainability standards. Using the Carhart and Fama-French frameworks, the study examines the influence of monthly ESG scores on excess returns for a sample of firms in developed European countries during the period January 2009 - December 2019. The findings, diverging from mainstream empirical research, show a negative effect of responsible conduct within firms. It can be inferred that a particular competitive disadvantage might occur from pouring capital towards sustainable initiatives through the opportunity cost of forgoing other prospects.